1999
DOI: 10.1038/sj.jhh.1000814
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of salt sensitivity testing using a dietary approach in essential hypertension

Abstract: To investigate the reproducibility of salt sensitivity testing using a dietary approach, 30 essential hypertensive patients underwent salt sensitivity testing on an outpatient basis twice with a 6 month interval. At both tests casual and 24-h ambulatory blood pressure (24-h BP) was recorded on habitual diet, then after a 6-day period on a low salt diet (aiming at 50 mmol/day), and finally after a 6-day period on a high salt diet (supplementation with sodium chloride tablets aiming at 250 mmol/day). Subjects sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…[17][18][19] Consistency in response was interpreted as poor, with intraclass correlation coefficients between two responses of 0.13 for ambulatory BP and 0.45 for clinic-measured mean arterial pressure. 17 Similarly, Gerdts et al 19 reported a nonsignificant correlation of 0.26 for casual and 0.02 for average 24-hour ambulatory BP when 30 participants underwent a saltsensitivity protocol twice. Other investigators reported weak statistics ranging from 0.24 to 0.38 17,18 when correlating the classifications of salt sensitivity and no salt sensitivity after conducting their protocol twice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] Consistency in response was interpreted as poor, with intraclass correlation coefficients between two responses of 0.13 for ambulatory BP and 0.45 for clinic-measured mean arterial pressure. 17 Similarly, Gerdts et al 19 reported a nonsignificant correlation of 0.26 for casual and 0.02 for average 24-hour ambulatory BP when 30 participants underwent a saltsensitivity protocol twice. Other investigators reported weak statistics ranging from 0.24 to 0.38 17,18 when correlating the classifications of salt sensitivity and no salt sensitivity after conducting their protocol twice.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators have interpreted data on reproducibility as either good [12][13][14][15][16] or poor. [17][18][19] Several factors may account for these contrasting interpretations, including participant differences across studies, varied duration of sodium intervention and amount of sodium levels given, sample size differences, lack of control of nutrients other than sodium, or lack of consensus as to what constitutes "good" reproducibility. Alternatively, one can view the mixed results as an indication that individual BP response to salt varies, in part randomly.…”
mentioning
confidence: 99%
“…10,11,18,33 In contrast to previous studies that used a single baseline measurement of urinary salt excretion or the average of the measurements on follow-up, 34 in our time-dependent Cox model we used, for the first time in this clinical setting, a cumulative average of sodium excretion. This is a gold-standard approach to model the relationship between longitudinally measured covariates and a given event 35 that has been extensively applied in Figure 4.…”
Section: Monitoring Salt Intakementioning
confidence: 99%
“…Inasmuch as this problem has been addressed, results are variable and there is certainly no stone-hard evidence that the phenomenon is reproducible. 5,6 However, the studies that have been done have included only a small number of individuals and spanned a relatively short period of time. Therefore, it is very fortunate and timely that this issue of Hypertension features a study by Gu et al 7 on the long-term reproducibility of salt-sensitivity testing.…”
Section: See Related Article P 499-505mentioning
confidence: 99%